A Critical Review of Symptom Management of Auditory Hallucinations in Patient with Schizophrenia - Suryani Suryani (Faculty of Nursing Universitas Padjadjaran, 2015)
Auditory hallucinations are a key symptom of schizophrenia. It is estimated that the prevalence of auditory hallucinations in people with schizophrenia range from 64.3% to 83.4%. The auditory hallucinations impacted on daily lives of the sufferer. An extensive review of the literature was undertaken to find symptom management that has been developed in reducing auditory hallucinations from CINAHL, PsyInfo, Health and Medical Complete, ProQuest Psychology Journals, ProQuest Social Journals, Science Direct, Web of Science and Scopus. Based on the analysis of the 15 articles, evidence was suggested that CBT and other psychological treatments have beneficial for individuals who experience auditory hallucinations. However, individuals who experience auditory hallucinations are not just sufferers who need to be treated but people who can develop their own strategies of living with auditory hallucinations. Therefore it is important for nurses to involve them in the management of the auditory hallucinations.Key words: Auditory hallucinations, literature review, symptom management. Reviu Kritis terhadap Pengelolaan Gejala Halusinasi Pendengaran pada Pasien SkizofreniaAbstrakHalusinasi pendengaran merupakan gejala utama skizofrenia. Prevalensi halusinasi pendengaran pada penderita skizofrenia diperkirakan berkisar antara 64,3% sampai 83,4%. Halusinasi pendengaran berdampak pada kehidupan sehari-hari penderitanya. Kajian literatur ini dilakukan untuk menemukan manajemen gejala yang telah dikembangkan dalam mengurangi halusinasi pendengaran dari CINAHL, PsycINFO, Kesehatan dan Kedokteran Lengkap, Jurnal Psikologi Proquest, Jurnal Sosial Proquest, Science Direct, Web of Science dan Scopus. Berdasarkan analisis terhadap dari 15 artikel, ada bukti yang menunjukkan bahwa CBT dan perawatan psikologis lainnya bermanfaat bagi individu yang mengalami halusinasi pendengaran dalam mengatasinya. Namun, individu yang mengalami halusinasi pendengaran bukan hanya penderita yang perlu diobati tetapi individu yang dapat mengembangkan strategi mereka sendiri hidup dengan halusinasi pendengaran. Karena itu penting bagi perawat untuk melibatkan mereka dalam manajemen halusinasi tersebut.Kata kunci: Halusinasi pendengaran, kajian literature, manajemen gejala.